Microstructure and hardness of Bi-modified magnesium AZ31 alloys subjected to severe plastic deformation - Yazdi, Javad; Farshidi, Mohammad Hassan; Ebrahimi, Gholamreza (Journal of Mining and Metallurgy, Section B: Metallurgy, 2025)
Magnesium alloys are known as attractive materials because of their low density and good thermal conductivity. However, compared to competing metallic materials such as aluminum alloys, magnesium alloys have lower strength. Among different methods introduced for strengthening metallic materials, severe plastic deformation is notable for its efficiency and relative simplicity. This study investigates the effect of bismuth content on the microstructure evolution and hardness of magnesium AZ31 alloy subjected to severe plastic deformation through equal channel angular pressing. For this purpose, AZ31 alloys with nominal bismuth contents of 0%, 1%, and 3% were processed by up to four passes of equal channel angular pressing at 300 °C. The microstructure evolution of these alloys was then examined using optical and scanning electron microscopy. The hardness of the specimens was measured using the Vickers method. Results show that bismuth-enriched second-phase particles are fragmented during severe plastic deformation. Additionally, increasing the bismuth content leads to more rapid grain refinement during severe plastic deformation due to the pinning effect of these second-phase particles on the grain boundaries. Faster hardening rates during severe plastic deformation were observed for the bismuth-containing AZ31 alloys. This effect is attributed to the more rapid grain refinement and the increase in the Hall-Petch coefficient resulting from the presence of fine bismuth-enriched particles.
Keywords: Magnesium AZ31 alloy; Bismuth addition; Severe plastic deformation; Grain refinement; Hardness